2004
DOI: 10.2527/2004.82102930x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of recombinant ovine leptin in growing beef heifers: Effects on secretion of LH, metabolic hormones, and timing of puberty1

Abstract: Serum concentrations of leptin increase linearly from approximately 16 wk before until the week of pubertal ovulation in beef heifers. To test the hypothesis that exogenous leptin can hasten the onset of puberty in heifers, we examined the effects of chronic administration of recombinant ovine leptin (oleptin) on timing of puberty, pulsatile and GnRH-mediated release of LH, and plasma concentrations of GH, IGF-I, and insulin. Fourteen fall-born, prepubertal heifers (Brahman x Hereford, 12 to 13 mo; 304.7+/-4.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
17

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
1
21
0
17
Order By: Relevance
“…infusion into ewes restricted for 6 months (23 kg below controls) restored LH (Henry et al, 2001). Yet Maciel et al (2004) infused ovine leptin into prepubertal heifers for 40 days and raised plasma leptin by 7 times but did not affect LH pulses, or mean LH, or induce puberty. Morrison et al (2001) found lower LH pulse frequency in restricted lambs than fed lambs and this did not change with i.c.v.…”
Section: Leptin and Reproductionmentioning
confidence: 99%
“…infusion into ewes restricted for 6 months (23 kg below controls) restored LH (Henry et al, 2001). Yet Maciel et al (2004) infused ovine leptin into prepubertal heifers for 40 days and raised plasma leptin by 7 times but did not affect LH pulses, or mean LH, or induce puberty. Morrison et al (2001) found lower LH pulse frequency in restricted lambs than fed lambs and this did not change with i.c.v.…”
Section: Leptin and Reproductionmentioning
confidence: 99%
“…The dose of leptin used in the current study (4.8 μg/kg BW twice daily or 9.6 μg/kg BW per day) was chosen based on a previous study by Maciel et al (2004a), in which chronic administration of oLeptin at 38.4 μg/kg BW per day for 40 d generated a linear increase in leptin concentrations of treated animals, reaching plasma concentrations values 35-fold greater in treated than nontreated animals. Therefore, we chose for the current study the lowest dose of oLeptin able to signifi cantly increase leptin concentrations above the nontreated group (9.6 μg/kg BW per day).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of leptin adopted in this study was based on previous studies with prepubertal heifers (Garcia et al, 2002;Maciel et al, 2004a). The aim was to raise serum leptin concentration to 5 to 10 ng/mL for a period of 8 to 12 h after a single injection.…”
Section: Hormonal Treatment and Reproductive Evaluationmentioning
confidence: 99%
“…Isso pode ser evidenciado em novilhas de corte submetidas a jejum, nas quais esse hormônio foi capaz de prevenir a redução na frequência de pulsos de LH e também aumentar a responsividade da hipófise anterior ao GnRH (MACIEL et al, 2004). Já em vacas de corte adultas em jejum, a leptina altera a secreção de GnRH e de LH (AMSTALDEN et al, 2002).…”
Section: Introductionunclassified
“…Já em vacas de corte adultas em jejum, a leptina altera a secreção de GnRH e de LH (AMSTALDEN et al, 2002). Porém, esses efeitos não são observados quando os animais têm suas necessidades nutricionais supridas (MACIEL et al, 2004;AMSTALDEN et al, 2005). Ao contrário do LH, o padrão de secreção de FSH parece não ser afetado pela subnutrição e pela consequente diminuição na leptinemia, possivelmente devido a uma menor influência do GnRH sobre a produção desse hormônio (PADMANABHAN & MCNEILLY, 2001).…”
Section: Introductionunclassified